2019
DOI: 10.1002/dta.2550
|View full text |Cite
|
Sign up to set email alerts
|

Application of a molecular networking approach for clinical and forensic toxicology exemplified in three cases involving 3‐MeO‐PCP, doxylamine, and chlormequat

Abstract: Untargeted toxicological screening is an analytical challenge, given the high number of molecules and metabolites to be detected and the constant appearance of new psychoactive substances (NPS). The combination of liquid chromatography with high-resolution tandem mass spectrometry (HRMS/MS) in a data-dependent acquisition mode generates a large volume of high quality spectral data. Commercial software for processing MS data acquired during untargeted screening experiments usually compare measured features (mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…Identification means were also of major importance in this study. For this purpose, we used validated process based on exact mass, mass spectra, retention times, fragmentation pattern analysis with SIRIUS 4.0.1 software, www.nature.com/scientificreports/ information propagation, and mass shifts corresponding to biotransformation reactions as already described 9,13,25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Identification means were also of major importance in this study. For this purpose, we used validated process based on exact mass, mass spectra, retention times, fragmentation pattern analysis with SIRIUS 4.0.1 software, www.nature.com/scientificreports/ information propagation, and mass shifts corresponding to biotransformation reactions as already described 9,13,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Each node represents an ion and its associated fragmentation spectrum, the links between the nodes indicating similarities between spectra. By allowing to propagate structural information within the network and facilitating sample-to-sample comparison, the MN approach offers valuable insights into drug metabolism 9 . Thereby, a multi-matrix approach provides a semi-quantitative visualization of molecule repartition in different matrix samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MN has been implemented in different fields, particularly metabolomics and drug discovery (Quinn et al, 2017); MN in forensic toxicology was previously used by Allard et al (2019) for the retrospective analysis of routine cases involving biological sample analysis. Yu et al (2019) also used MN analysis for the detection of designer drugs such as NBOMe derivatives and they showed that unknown compounds could be recognized as NBOMe-related substances by MN.…”
Section: Introductionmentioning
confidence: 99%